Moderate Colitis Not Requiring Intravenous Steroids Is Associated with Improved Survival in Stage IV Melanoma after Anti-CTLA4 Monotherapy, But Not Combination Therapy. (6th June 2022) - Anstadt, Emily J; Chu, Brian; Yegya-Raman, Nikhil; Han, Xiaoyan; Doucette, Abigail; Poirier, Kendra; Mohiuddin, Jahan J; Maity, Amit; Facciabene, Andrea; Amaravadi, Ravi K; Karakousis, Giorgos C; Cohen, Justine V; et al.
Abstract: Background: For patients with melanoma, gastrointestinal immune-related adverse events are common after receipt of anti-CTLA4 therapy. These present difficult decision points regarding whether to discontinue therapy. Detailing the situations in which colitis might predict for improved survival and how this is affected by discontinuation or resumption of therapy can help guide clinical decision-making. Materials and Methods: Patients with stage IV melanoma receiving anti-CTLA4 therapy from 2008 to 2019 were analyzed. Immune-related colitis treated with ≥50 mg prednisone or equivalent daily or secondary immunosuppression was included. Moderate colitis was defined as receipt of oral glucocorticoids only; severe colitis was defined as requiring intravenous glucocorticoids or secondary immunosuppression. The primary outcome was overall survival (OS). Results: In total, 171 patients received monotherapy, and 91 received dual checkpoint therapy. In the monotherapy group, 25 patients developed colitis and a nonsignificant trend toward improved OS was observed in this group. Notably, when colitis was categorized as none, moderate or severe, OS was significantly improved for moderate colitis only. This survival difference was not present after dual checkpoint therapy. There were no differences in known prognostic variables between groups, and on multivariable analysis neither completion of all ipilimumab cycles nor resumption of immunotherapy correlated with OS, while the development of moderate colitis did significantly affect OS. Conclusion: This single-institution retrospective series suggests moderate colitis correlates with improved OS for patients with stage IV melanoma treated with single-agent anti-CTLA4, but not dual agent, and that this is true regardless of whether the immune-checkpoint blockade is permanently discontinued. Abstract : Gastrointestinal immune-related adverse events are common in patients with melanoma who have received anti-CTLA4 therapy. This presents difficult decisions regarding whether to discontinue therapy. This study focused on situations in which colitis might predict for improved survival and how continuation or termination of therapy can help guide clinical decision-making.